International Registry on Factor XIII Deficiency: A basis formed mostly on European data - Ivaskevicius, Vytautas; Seitz, Rainer; Kohler, Hans P.; Schroeder, Verena; Muszbek, Laszlo; Ariens, Robert A. S.; Seifried, Erhard; Oldenburg, Johannes; and The Study Group (Thrombosis and Haemostasis, 2007)
FXIII deficiency is known as one of the rarest blood coagulation disorders. In this study, the phenotypic and in part genotypic data of 104 FXIII-deficient patients recorded from 1993 – 2005 are presented. The most common bleeding symptoms were subcutaneous bleeding (57%) followed by delayed umbilical cord bleeding (56%), muscle hematoma (49%), hemorrhage after surgery (40%), hemarthrosis (36%), and intracerebral bleeding (34%). Prophylactic treatment was initiated in about 70% of all patients. FXIII-B subunit-deficient patients had a milder phenotype than patients with FXIII-A subunit deficiency. The most frequent mutation affecting the F13A gene was a splice site mutation in intron 5 (IVS5–1G>A). This mutation was found in eight (17%) of 46 analyzed families. The haplotype analysis of patients carrying the IVS5–1A allele was consistent with a founder effect. The international registry (http://www.f13-database.de) will provide clinicians and scientists working on FXIII deficiency with a helpful tool to improve patient care and direct future studies towards better understanding and treatment of the disease.
Keywords: FXIII deficiency; phenotyping; genotyping; International FXIII Registry